Enterprise Architecture Planning Using TOGAF Version 9 (Case Study Of Badan Pengelolaan Pendapatan Daerah Kab.Sumedang) - Dian Hermawan; Fathoni Mahardika; Yopi Hidayatul Akbar (STMIK PONTIANAK, 2020)
Bappenda currently utilizes Information Systems as the main driver in its activities which include the process of registration, data collection, determination, acceptance, billing, and reporting, in supporting its activities Bappenda needs to have an Information System strategic planning that can identify computer-based application portfolios in carrying out business processes, by therefore we need a tool that can be used to provide a basic organizational structure for the company as a whole using Enterprise Architecture. The method used in architectural planning is The Open Group Architecture Framework (TOGAF), which can provide techniques on how to build, manage and implement enterprise architecture and information systems called the Architecture Development Method (ADM). Based on the results of the study, it can be concluded that the application of the TOGAF method in Bappenda can improve the performance of the system applied by a percentage of 57.29%. The suggestion for implementing TOGAF in Bappenda is to be able to develop gradually according to the existing stages in TOGAF and explain how to find an organization's enterprise architecture specifically based on business needs and processes